MEASUREMENT OF INTEREST RATE AND PERIOD USING LOGARITHM EQUATIONS: A STUDY OF TIME VALUE OF MONEY - Nainggolan, Rexon (Universitas PGRI Madiun, 2024)
ABSTRACT The primary aim of this study is to illustrate how logarithmic calculation and equation can effectively replace traditional table usage and interpolation techniques in time value of money calculations. It proposes the application of algorithmic computation to calculate the interest rate and period when the future value and present value are known. It developed and formulated two primary equations utilizing an algorithmic approach as an alternative to the conventional reliance on financial tables and linear interpolation prevalent in the existing literature. The two methods are validated and substantiated upon reevaluating the fundamental time value of money calculation, yielding far more precise results than the traditional method. The measurement can also be utilized in the statistical realm to compute the compounded average yearly growth or growth period when other parameters are available. ABSTRAK Tujuan utama dari studi ini adalah untuk memberikan ilustrasi bagaimana perhitungan dan persamaan logaritma dapat secara efektif menggantikan penggunaan tabel tradisional dan teknik interpolasi dalam perhitungan nilai waktu uang. Studi ini mengusulkan penerapan perhitungan algoritma untuk menghitung suku bunga dan periode waktu ketika nilai masa depan dan nilai kini diketahui. Studi ini mengembangkan dan merumuskan dua rumus utama yang memanfaatkan pendekatan algoritma sebagai alternatif dari ketergantungan konvensional pada tabel keuangan dan interpolasi linier yang lazim dalam literatur yang tersedia. Kedua metode tersebut tervalidasi dan setelah mengevaluasi ulang perhitungan nilai waktu uang ke rumus dasarnya, menghasilkan hasil perhitungan yang lebih akurat daripada metode tradisional. Pengukuran tersebut juga dapat digunakan pada bidang statistik untuk menghitung pertumbuhan tahunan rata-rata atau periode pertumbuhan ketika parameter lain tersedia.